Benefit of Catheter Ablation for Atrial Fibrillation in Heart Failure Patients with Different Etiologies - Songbing Long; Yuanjun Sun; Xianjie Xiao; Zhongzhen Wang; Wei Sun; Lianjun Gao; Yunlong Xia; Xiaomeng Yin (Journal of Cardiovascular Development and Disease, 2023)
(1) Background: A plethora of studies have elucidated the safety and efficacy of catheter ablation (CA) for patients afflicted with atrial fibrillation (AF) and concomitant reduction in left ventricular ejection fraction (LVEF). Nevertheless, the literature on the benefits of CA in the specific etiological context of heart failure (HF) remains limited. This study delineates a comparative assessment of outcomes for patients with AF and reduced LVEF across the primary etiologies. (2) Methods: Our inquiry encompassed 216 patients diagnosed with congestive heart failure and an LVEF of less than 50 percent who were referred to our institution for circumferential pulmonary vein isolation (CPVI) between the years 2016 and 2020. The selection criteria included a detailed medical history while excluding those suffering from valvular disease, congenital heart disease, and hypertrophic cardiomyopathy. In an effort to scrutinize varying etiologies, patients were stratified into three categories: dilated cardiomyopathy (DCM, n = 56, 30.6%), ischemic cardiomyopathy (ICM, n = 68, 37.2%), and tachycardia-induced cardiomyopathy (TIC, n = 59, 32.2%). (3) Results: Following an average (±SD) duration of 36 ± 3 months, the prevalence of sinus rhythm was 52.1% in the DCM group, 50.0% in the ICM group, and 68.14% in the TIC group (p = 0.014). This study revealed a significant disparity between the DCM and TIC groups (p = 0.021) and the ICM and TIC groups (p = 0.007), yet no significant distinction was discerned between the TIC and ICM groups (p = 0.769). Importantly, there were no significant variations in the application of antiarrhythmic drugs or recurrence of procedures among the three groups. The mortality rates were 14.29% for the DCM group and 14.71% for the ICM group, which were higher than the 3.39% observed in the TIC group (DCM vs. TIC p = 0.035 (HR = 4.50 (95%CI 1.38–14.67)), ICM vs. TIC p = 0.021 (HR = 5.00 (95%CI 1.61–15.50))). A noteworthy enhancement in heart function was evidenced in the TIC group in comparison to the DCM and ICM groups, including a higher LVEF (p < 0.001), diminution of LV end-diastolic diameter (p < 0.001), and an enhanced New York Heart Association classification (p = 0.005). Hospitalization rates for heart failure were discernibly lower in TIC patients (0.98 (0,2) times) relative to those with DCM (1.74 (0,3) times, p < 0.01) and TIC (1.78 (0,4) times, p < 0.001). Patients with paroxysmal atrial fibrillation and brief episodes were found to achieve superior clinical outcomes through a catheter ablation strategy. (4) Conclusion: Patients diagnosed with TIC demonstrated a more pronounced benefit from catheter ablation compared to those with DCM and ICM. This encompassed an augmented improvement in cardiac function, an enhanced maintenance of sinus rhythm, and a reduced mortality rate.